2013
DOI: 10.1002/pssr.201350509
|View full text |Cite
|
Sign up to set email alerts
|

Frontispiece: Evidence of two‐photon absorption in strain‐free quantum dot GaAs/AlGaAs solar cells (Phys. Status Solidi RRL 3/2013)

Abstract: To accommodate the need of energy‐related research for quality publications that keep the pace, pss (RRL) expands its coverage of photovoltaics and solar cells in a new regular section rrl solar, see the Rapid Research Letter by Andrea Scaccabarozzi et al. in this issue (). rrl solar calls for Rapid Research Letter and Review@RRL contributions in the following areas: • Photovoltaic materials preparation, optimization, characterization and physics • Significant solar cell advances, modeling or characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was reported that DE allows the selforganization of strain-free GaAs QDs in AlGaAs barriers [17]. Two-photon absorption in strain-free GaAs/AlGaAs QDSCs grown via the DE method was confirmed [18]. While there are still opening questions to address to make QDSCs more efficient solar cells, such as the open-circuit voltage (V oc ) degradation and marginal photocurrent contribution from QDs, solar cells based on strain-free QDs are expected to improve cell performance because of the alleviation of strain-induced defects.…”
Section: Introductionmentioning
confidence: 85%
“…It was reported that DE allows the selforganization of strain-free GaAs QDs in AlGaAs barriers [17]. Two-photon absorption in strain-free GaAs/AlGaAs QDSCs grown via the DE method was confirmed [18]. While there are still opening questions to address to make QDSCs more efficient solar cells, such as the open-circuit voltage (V oc ) degradation and marginal photocurrent contribution from QDs, solar cells based on strain-free QDs are expected to improve cell performance because of the alleviation of strain-induced defects.…”
Section: Introductionmentioning
confidence: 85%